Diode laser versus blunt dissection tonsillectomy (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Tonsillectomy is the commonest operation performed in Ear, Nose and Throat Department. Various methods of tonsillectomy have been practiced over the century aimed at  reducing or eliminating intra-operative and postoperative morbidity.Aim: This prospective study is aimed at evaluation of advantages and disadvantages of laser tonsillectomy over blunt dissection tonsillectomy in respect of operative time, intra-operative blood loss, postoperative pain, rate of healing of tonsillar fossa and other postoperative complications.Method: This prospective randomized study was done for 18 months from April 2010 to September 2011.One hundred patients were divided into two groups of equal number. In one group, the tonsillectomy performed by Diode laser and in the other group the tonsillectomy performed by conventional dissection technique.Results: Age ranged from 5 - 34 years with mean age 15.4 in laser group and 4-35 years with mean age 15.98 in dissection group. Operative time and amount of blood loss is significantly reduced in the laser group (10-25 min, mean 12 min in laser group, 15-45 min, and mean 25 min in dissection group). Tonsillectomy by using laser has shown less intra-operative bleeding (5ml-20 ml, mean 10 ml compared with 45-250 ml, mean 70 ml in dissection method). Patients experienced mild to moderate pain in laser group and moderate to severe pain in dissection group in first 24-48 hours. Pain increased in intensity after 5-6 days in laser group. On 8th post operative day thin to thick white coating is observed with smooth tonsillar fossa in laser group whereas granulation tissue is observed in dissection group.Conclusion: In conclusion laser tonsillectomy has some advantages over dissection method.  There is less operative time and intra-operative bleeding and less immediate post operative pain. Disadvantage of laser tonsillectomy is that there is more pain in 5th to 6th post operative period this may be due to thick slough formation. DOI:http://dx.doi.org/10.3329/bjo.v18i2.11983 Bangladesh J Otorhinolaryngol 2012; 18(2): 114-118